"Superdisabilities" vs "disabilities"? Theorizing the role of ableism in (mis)representational mythology of disability in the marketplace. Issue 5 (2nd November 2019) - Kearney, Shauna; Brittain, Ian; Kipnis, Eva
ABSTRACT: People with disabilities (PWD) constitute one of the largest minority groups. While recognition and inclusion of this group in the marketplace has seen improvement, the effects of (mis)representation of PWD in shaping the discourse on fostering marketplace inclusion of socially marginalized consumers remain little understood. By extending the theory of ableism into the context of PWD representation and applying it to the analysis of the We're the Super humans advertisement developed for the Rio 2016 Paralympic Games, this paper examines the relationship between the (mis)representation and the inclusion/exclusion discourse. By uncovering that PWD misrepresentations can partially mask and/or redress the root causes of exclusion experienced by PWD in their lived realities, it contributes to the research agenda on the transformative role of consumption cultures perpetuating harmful, exclusionary social perceptions of marginalized groups versus contributing to advancement of their inclusion.